Preventing Islamic Radicalism Through Integrative Epistemology Of Sadrian Philosophy: The Case Study of Hizbut Tahrir Indonesia’s Reasoning - Rahman, Fadhlu; Nuraripah, Pia; Layyinah, Rahmatika (Analisis: Jurnal Studi Keislaman, 2018)
Intolerance and radicalism in Indonesia achieve dangerous staging status. This condition in individual aspects have an influence on the way of view that will tend to be defensive, apologist and pessimistic in religion. This also becomes the initial cause for the birth of social, political and educational implications. HTI (Hizbut-Tahrir Indonesia) is a radical mass organization that is quite influential in Indonesia. The epistemological problem related to the theory of knowledge is one of the important and fundamental factors in the emergence of understanding and various acts of radicalism in HTI, where it only recognizes thinking by relying on factual objects as the only valid knowledge that leads to empiricism and materialism so that it rejects the form of spiritual knowledge that is able to accept diversity in opinion. In addition to these fundamental reasons, Sufism is also often considered to be heretical because it is not committed to the Qur'an and Sunnah. It is thus necessary for an integrative understanding between the three epistemological elements (Textual, spiritual, and rational) as the building blocks of deradicalization in religion as well as a strong commitment to the Qur'an and al-Sunnah. A descriptive analysis of Mulla Sadra's epistemology as a philosopher and Sufi can be one of the cornerstones of criticism as well as a solution to the problem of HTI's radical epistemology. This is reflected in the integration of the three methods (textual, spiritual and rational) which he uses as a way of knowing the nature of things. Thus, the thesis that we can propose is to use Sadra's integrative epistemology in gaining knowledge will avoid an understanding of HTI’s radicalism.